Effect of seawater on hydration and sulfate resistance of noncement mortars - Liu,S-Q; Wu,C; Wang,D-M; Guo,J-P; He,L (Journal of Materials in Civil Engineering, 2022)
Modern concrete construction consumes significant amounts of freshwater, which is a valuable natural resource. Using seawater can be an alternative solution to reduce freshwater consumption for sustainable development. The durability of seawater construction materials should be studied for better understanding of their long-term behavior. This study investigated the effect of seawater on the hydration and the sulfate resistance of noncement mortars prepared by mixing ground granulated blast furnace slag (BFS), carbide slag (CS), and silica fume (SF) to understand the feasibility of using seawater and solid waste materials to develop low-carbon construction materials. CS in the mix acted as an alkali activator for the hydration and strength development of the solid wastes. Two batch specimens were prepared, one batch mixed with seawater and the other mixed with freshwater for comparison. A compressive test investigated the effect of seawater on the mechanical properties. Heat flow, X-ray diffractometry (XRD), and thermogravimetry tests were used to understand the hydration. The results suggest that the seawater could accelerate the hydration by producing a large amount of hydrocalumite, which improves the compressive strength at early ages. Durability testing was carried out by immersing specimens in a sulfate solution for various durations. Sulfate resistance was characterized by XRD, and ettringite and Friedel’s salt were the main corrosion products when the specimens were immersed in sulfate solution. Corrosion could be reduced by seawater in the specimens. Scanning electron microscopy was used to characterize the microstructure of the hydration products, which showed that the corrosion was a progressive process. A loose and porous microstructure of the specimen surface accelerated corrosion of the noncement specimens.